2021
DOI: 10.1088/1755-1315/651/3/032106
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation model of coal mine emergency rescue resource allocation based on weight optimization TOPSIS method

Abstract: In order to solve the problems of unreasonable allocation and low efficiency of emergency rescue resources in coal mine accidents, it is necessary to establish a coal mine emergency rescue resource allocation model by using comprehensive weight-approximation ideal solution (TOPSIS method).This paper takes rock burst in a coal mine as an example by extending this designed emergency rescue plan. Firstly, calculated the weight of the evaluation index affecting the emergency rescue is selected by AHP method and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…The comprehensive weighting method (CWM) is based on the principle of information entropy, which combines the subjective weight method and objective weight method to allocate a more reasonable comprehensive weight. The calculation formulas are as follows 28 , 29 where ω j refers to the value of the comprehensive weight, ω 1 j refers to the value of the subjective weight, and ξ j refers to the value of the objective weight.…”
Section: Research Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The comprehensive weighting method (CWM) is based on the principle of information entropy, which combines the subjective weight method and objective weight method to allocate a more reasonable comprehensive weight. The calculation formulas are as follows 28 , 29 where ω j refers to the value of the comprehensive weight, ω 1 j refers to the value of the subjective weight, and ξ j refers to the value of the objective weight.…”
Section: Research Methodologymentioning
confidence: 99%
“…The comprehensive weighting method (CWM) is based on the principle of information entropy, which combines the subjective weight method and objective weight method to allocate a more reasonable comprehensive weight. The calculation formulas are as follows 28,29 Z min (ln ln ) (ln ln )…”
Section: Methodsmentioning
confidence: 99%
“…This method is widely used in multi-objective scheme selection, such as for highways, electric power, etc. [17,[36][37][38][39].…”
Section: Plos Onementioning
confidence: 99%
“…To date, several studies have deeply investigated the ER measures of coal mine accidents [7,8]. The ER communication system can effectively improve the monitoring accuracy and the efficiency of searching dangerous situations [9]. It is found that the emergency stations covering all mining areas are set up underground to provide medical first aid and transportation of injured in the shortest time [10].…”
Section: Introductionmentioning
confidence: 99%